(untitled) (VERITAS LEGIS JOURNAL, 2026)
This article examines the current challenges of law enforcement practice in regulating labor and civil law relations arising in the Republic of Kazakhstan in the context of the development of platform employment. Particular attention is paid to the transformation of traditional labor relations under the influence of the digital economy and the expansion of online platforms, including taxi aggregators. The study analyzes the criteria for distinguishing between labor and civil law relations, as well as issues related to determining the legal status of individuals engaged in work through digital platforms. The research includes an analysis of the current legislation of the Republic of Kazakhstan, identifying existing legal gaps and inconsistencies in the regulation of platform employment. Special emphasis is placed on the issues of social protection of workers, including guarantees of employment, remuneration, occupational safety, and access to mechanisms for protecting labor rights. In addition, the article examines foreign experience in regulating platform employment, particularly approaches to classifying workers’ legal status and ensuring their rights. The findings demonstrate that the legal regulation of platform employment in Kazakhstan remains insufficiently developed, despite its rapid growth in the context of digitalization. The study substantiates the need to improve national legislation and develop comprehensive legal mechanisms aimed at ensuring a balance of interests between workers, digital platforms, and the state.